PEMASARAN BISNIS MADU HUTAN AMFOANG DENGAN PENDEKATAN RANTAI NILAI - Dina V. Sinlae; Lewi Bentang; Melgiana S. Medah; Welianto Boboy (Partner, 2023)
This research was conducted in Kupang Regency and Kupang City by interviewing 23 farmers, four collectors, two processors, and one supporting agency with the aim of analyzing the marketing aspect of honey from Amfoang using a value chain approach. The results showed, marketing chain of forest honey was relatively long and involved many actors, which resulted in low share received by farmers (13.79%). Meanwhile, the largest profit margins were among the retailer in NTT and retailers outside NTT at 33.8% and 36%, respectively. It is suggested that there is a need to increase the honey quality by empowering forest honey business actors, especially upstream players and shortening the marketing channels by optimizing marketing models based on digital technology. Key Words: Marketing analysis, honey, Amfoang, value chain approach